Hubungan Status Gizi dengan Kejadian Anemia pada Remaja Putri di SMAN 1 Solor Selatan - Anastasia Tapololon Tukan; Widia Shofa Ilmiah (Published by Institut Teknologi Pendidikan Indonesia, 2026)
Anemia remains a common health issue among adolescent girls and continues to pose a significant challenge, especially in developing nations. Various factors have been linked to the development of anemia, one of which is nutritional status. This study was conducted to investigate whether nutritional status is associated with anemia among female adolescents enrolled at SMAN 1 South Solor. The research applied a quantitative approach using a descriptive-correlational design with a cross-sectional framework. Eighty-six female students were recruited through purposive sampling.Assessment of nutritional status was carried out using anthropometric measurements, including body weight and height, while hemoglobin concentrations were determined using a hemoglobin analyzer. The relationship between the variables was examined using Fisher’s Exact Test. The results indicated that nearly all participants were classified as having normal nutritional status (97.7%), and most of them did not suffer from anemia (59.3%). Statistical testing produced a p-value of 0.0512, which exceeded the significance level of 0.05, suggesting that no significant association existed between nutritional status and anemia among the study participants. These findings imply that nutritional status alone may not be a determining factor for anemia in adolescent girls. Other contributing factors, such as iron consumption, dietary practices, and menstrual-related conditions, may have a greater influence on the occurrence of anemia in this population.